2019
DOI: 10.17159/2078-5151/2019/v57n3a2863
|View full text |Cite
|
Sign up to set email alerts
|

A one year audit of the Colorectal Unit at Wits Donald Gordon Medical Centre: 2016–2017

Abstract: Background: Colorectal surgery has developed into an established surgical subspecialty in South Africa, however there is a paucity of data regarding the epidemiology and surgical outcomes of patients with colorectal disease in this country. The objective is to present the findings of a one-year audit of the Wits Donald Gordon Medical Centre (WDGMC) Colorectal Unit with specific reference to indications, surgical procedures and patient outcomes. Methods: Patient files from December 2016 to November 2017 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the present study, the POI incidence rate seen in the study population was 36% (56 POI out of 155 cases) which was higher than anticipated (refer to Table 1). The incidence rate previously reported at the same institution was 13,7% (19 POI out of 139 elective colorectal resections between December 2016 to November 2017) (20). The POI incidence rate reported in a literature review of 11 studies ranged between 2 and 54%, with the median incidence rate reported as 10,3% after colorectal surgery (5).…”
Section: Poi Incidencementioning
confidence: 86%
See 3 more Smart Citations
“…In the present study, the POI incidence rate seen in the study population was 36% (56 POI out of 155 cases) which was higher than anticipated (refer to Table 1). The incidence rate previously reported at the same institution was 13,7% (19 POI out of 139 elective colorectal resections between December 2016 to November 2017) (20). The POI incidence rate reported in a literature review of 11 studies ranged between 2 and 54%, with the median incidence rate reported as 10,3% after colorectal surgery (5).…”
Section: Poi Incidencementioning
confidence: 86%
“…The high incidence of POI at the study hospital was identified in the previous study as one of the reasons for prolonged LOS at the institution and some postoperative components of ERAS including limitation of fluid and opioid-sparing strategies were implemented at the study hospital ( 20 ). Due to challenges like high cost and a shortage in resources in SA ( 44 ), full implementation of all ERAS components has not been possible yet ( 20 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this exclusion does not represent a source of significant bias in sampling, as the rate of major complications in the WDGMC CRU for the study period was approximately 7.8%, which is consistent with international complication rates. 22 MARCH 2022…”
Section: Methodsmentioning
confidence: 99%